Predicting reading comprehension on the Internet: Contributions of offline reading skills, online reading skills, and prior knowledge - Coiro, Julie (Journal of Literacy Research, 2011)
This study investigated the extent to which new reading comprehension proficienciesmay be required when adolescents read for information on the Internet. Seventh graders( N=109) selected from a stratified random sample of diverse middle school students completed a survey of topic-specific prior knowledge and parallel scenario-based measures of online reading comprehension. Standardized reading comprehension scores were also collected. Results indicated performance on one measure of online reading comprehension accounted for a significant amount of unique variance in performance on a second measure of online reading comprehension after controlling for standardized test scores of offline reading comprehension and topic-specific prior knowledge. Furthermore, there was an interaction between priorknowledge and online reading comprehension, such that higher levels of onlinereading comprehension skills may help compensate for lower levels of topic-specificprior knowledge when adolescents are asked to locate, critically evaluate, synthesize,and communicate information using the Internet. The author discusses a series of alternative interpretations of the data as well as their implications for literacy theoryand research. Keywords : comprehension processes, digital literacy, new literacies, online reading and writing,prior knowledge, background knowledge, schema
Keywords: compréhension; digital literacy/ies; écriture et lecture numériques; lecture numérique